A qualitative study on adolescents’ perceptions of the Bepupur Ritual among the Tidung Tribe in Malinau Village - Supardiansyah Supardiansyah; Moh Bahzar; Alim Salamah; Endang Herliah (Satwika : Kajian Ilmu Budaya dan Perubahan Sosial, 2025)
This study explores adolescents’ perceptions of the bepupur ritual, a pre-marital purification ceremony practiced by the Tidung people in Malinau Kota Village. Amid the forces of modernization, preserving local culture poses a considerable challenge, particularly in engaging the younger generation. The research employs a qualitative approach, with data collected through direct observation and in-depth interviews involving eight informants—six adolescents and two traditional leaders. Data validity was ensured through source and technique triangulation, and analysis was conducted using the Miles and Huberman model. The findings indicate that most adolescents hold positive perceptions of the ritual, viewing it as a sacred symbol of cultural identity. These results highlight the vital role of the younger generation in sustaining this tradition. The novelty of this research lies in its focus on adolescents as active agents in cultural preservation, contributing to the broader discourse on local identity within the context of social transformation.   Penelitian ini bertujuan untuk mengkaji persepsi remaja terhadap ritual bepupur, yaitu prosesi penyucian diri menjelang pernikahan dalam tradisi adat Suku Tidung di Desa Malinau Kota. Di tengah arus modernisasi, pelestarian budaya lokal menjadi tantangan yang signifikan, terutama dalam melibatkan generasi muda. Penelitian ini menggunakan pendekatan kualitatif dengan pengumpulan data melalui observasi langsung dan wawancara mendalam terhadap delapan informan yang terdiri atas enam remaja dan dua tokoh adat. Validitas data diuji menggunakan triangulasi sumber dan teknik, sementara analisis dilakukan dengan model Miles dan Huberman. Hasil penelitian menunjukkan bahwa sebagian besar remaja memiliki persepsi positif terhadap ritual tersebut dan memandangnya sebagai simbol kesakralan serta identitas budaya. Temuan ini menegaskan pentingnya peran generasi muda dalam menjaga keberlanjutan tradisi. Kebaruan penelitian ini terletak pada fokusnya terhadap generasi muda sebagai agen aktif pelestarian budaya, serta kontribusinya terhadap kajian identitas lokal dalam konteks perubahan sosial.